Respuesta :
Answer:
x = [tex]\frac{y-4}{7}[/tex]
Step-by-step explanation:
Given
y = 7x + 4 ( subtract 4 from both sides )
y - 4 = 7x ( divide both sides by 7 )
[tex]\frac{y-4}{7}[/tex] = x
To change the expressions into another form of variable, we need to apply some basic mathematical operations to it. Thus, the final expression for x is [tex]\bold{x}=\bold{\dfrac{y-4}{7}}[/tex].
We need to interchange the dependent variable into the independent variable.
The given expression is [tex]\bold{y=7x+4}[/tex].
Now, take the given expression and solve it for variable x.
[tex]\begin{aligned} &\bold{y}=\bold{7x+4}\\&y-4=7x\\&x=\dfrac{y-4}{7} \end{aligned}[/tex]
Hence, the required expression is [tex]\bold{x}=\bold{\dfrac{y-4}{7}}[/tex].
To know more about it, please refer to the link:
https://brainly.com/question/22404695